A depth illusion supports the model of General Object Constancy: Size and depth constancies related by a same distance-scaling factor. (December 2016) - Qian, Jiehui; Petrov, Yury
Highlights: A new illusion of depth induced by a pattern of radial optic flow is reported. The illusory effects can be explained by General Object Constancy model. A same scaling factor is used to account for size and depth variations with distance. The apparent size contributes to scaling of depth signals to achieve constancy. Abstract: Perceptual constancy refers to the ability to stabilize the representation of an object even though the retinal image of the object undergoes variations. In previous studies, we proposed a General Object Constancy (GOC) hypothesis to demonstrate a common stabilization mechanism for perception of an object's features, such as size, contrast and depth, as the perceived distance varies. In the present study, we report another depth illusion supporting the GOC model. The stimuli comprised pairs of disks moving in a pattern of radial optic flow. Each pair consisted of a white disk positioned upper left to a dark disk, creating a percept of the white disk casting a shadow. As the pairs contracted towards the center of the screen in accordance with motion away from the observer, the two disks in each pair appeared to increase in contrast and separate farther away from each other both in the fronto-parallel plane (angular separation illusion) and in depth (depth separation illusion). While the contrast illusion and the angular separation illusion, which is a variant of the size illusion, replicated our previous findings, the illusion of depth separation revealed a depth constancy phenomenon. We further confirmed that the size and depth perception were related, e.g., the depth separation and the angular separation illusions were highly correlated across observers. Whereas the illusory increase in the angular separation between a disk and its 'shadow' could not be canceled by modulation of depth, decreasing the angular separation could offset the illusory increase in depth separation. The results can be explained by the GOC hypothesis: the visual system uses the same scaling factor to account for contrast, size (angular separation), and depth variations with distance; additionally, the perceived size of the object is used to scale its depth and contrast signals in order to achieve constancy.